2008
DOI: 10.1080/10408390701724371
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Heat Resistance Parameters of Bacterial Spores from their Survival Ratios at the End of UHT and other Heat Treatments

Abstract: Accurate determination of bacterial cells or the isothermal survival curves of spores at Ultra High Temperatures (UHT) is hindered by the difficulty in withdrawing samples during the short process and the significant role that the come up and cooling times might play. The problem would be avoided if the survival parameters could be derived directly from the final survival ratios of the non-isothermal treatments but with known temperature profiles. Non-linear inactivation can be described by models that have at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…(6) is valid only for a fixed value of the parameter b. Indeed, it has been previously reported that the parameter b is practically constant over the lethal temperature range (Mafart et al, 2002;Peleg et al, 2008). Therefore, in this study, for the global optimisation, Eq.…”
Section: Weibull Modelmentioning
confidence: 95%
“…(6) is valid only for a fixed value of the parameter b. Indeed, it has been previously reported that the parameter b is practically constant over the lethal temperature range (Mafart et al, 2002;Peleg et al, 2008). Therefore, in this study, for the global optimisation, Eq.…”
Section: Weibull Modelmentioning
confidence: 95%
“…(Equation 7 can also be converted into a difference equation and solved with general-purpose software like MS Excel [19].) The validity of the WeLL model has been demonstrated by its ability to correctly predict dynamic inactivation patterns from experimental isothermal survival data (6,16,24) or from dynamic data not used in its parameter calculations (4,17,20).…”
mentioning
confidence: 99%
“…The temperature dependence of the "rate parameter," b(T), can be described by the empirical log-logistic model (16,17,20):…”
mentioning
confidence: 99%
“…Moreover, Eq. 20.12 can be used not only to simulate and correctly predict dynamic inactivation patterns (e.g., Corradini and Peleg, 2004;Periago et al, 2004;Pardey et al, 2005;Peleg, 2006), but also to serve as a model for extracting the survival parameters, n, k and T c , from experimental survival curves determined under non-isothermal conditions Peleg, 2006;Peleg et al, 2008a;Corradini et al, 2008Corradini et al, , 2009a. A modified version of the WeLL model, could also be used to correctly predict dynamic survival patterns in chemical disinfection and there is evidence that it might be applicable to HHP as well (Corradini and Peleg, 2003b;Doona et al 2007).…”
Section: The Role Of Temperaturementioning
confidence: 99%